A numerical study of thermo-diffusion, diffusion-thermo and chemical reaction effects on flow of a micropolar fluid in an asymmetric channel with dilating and contracting permeable walls. Issue 2 (18th April 2017) - Mohyud-din, Syed Tauseef; Ahmed, Naveed; Khan, Umar; Rashidi, Mohammad Mehdi
Abstract : Purpose: The purpose of this study is to analyze thermo-diffusion and diffusion-thermo effects, combined with first-order chemical reaction, in the flow of a micropolar fluid through an asymmetric channel with porous boundaries. Suction/injection velocities of upper and lower walls are taken to be different from each other. The channel exhibits a parting or embracing motion and the fluid enters, or leaves, the channel because of suction/injection through the permeable walls. Design/methodology/approach: The solution of the problem is obtained by using the fourth-order Runge-Kutta method combined with the shooting technique. Findings: The asymmetric nature of the channel that is caused by the different permeabilities of the walls deeply influences the flow. The temperature of the fluid rises significantly by increasing the absolute value of A for both Case I and Case II. While, for the concentration profile, the concentration drops near the lower vicinity of the center in Case I, and, it falls near the lower wall of the channel in Case II. Stronger Dufour effects increase the temperature of the fluid except for Case 1 at the center of the channel and for Case II in lower quarter of the channel. Originality/value: It is confirmed that the presented work is original and is not under consideration by any other journal.